2004
DOI: 10.1042/cs20030376
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic neural hyperactivity and its normalization following unstable angina and acute myocardial infarction

Abstract: Impaired autonomic function occurs after AMI (acute myocardial infarction) and UA (unstable angina), which may be important prognostically. However, the pattern of sympathetic nerve hyperactivity has been investigated only after AMI. We aimed to quantify central sympathetic output to the periphery in patients with UA, investigate its progress over time relative to that after uncomplicated AMI and to explore the mechanisms involved. Muscle sympathetic nerve activity (MSNA) assessed from multiunit discharges and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 35 publications
1
43
0
3
Order By: Relevance
“…However, in such cases there is a tendency for central respiratory events to occur, which did not appear in our results since patients with cardiac failure were excluded. Another explanation may be inflammatory changes and sympathetic neural hyperactivity associated with ACS, 33 which could lead to destabilization of ventilatory control, affecting upper airway patency as well as chest wall muscles. 34 Considering that smoking is a predisposing factor for OSAHS, 35 an apparent explanation for the observed decrease of AHI 6 months later is that 12 of 16 current smokers in our study stopped smoking, with most of them included in the group of the 22 with decreased AHI 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…However, in such cases there is a tendency for central respiratory events to occur, which did not appear in our results since patients with cardiac failure were excluded. Another explanation may be inflammatory changes and sympathetic neural hyperactivity associated with ACS, 33 which could lead to destabilization of ventilatory control, affecting upper airway patency as well as chest wall muscles. 34 Considering that smoking is a predisposing factor for OSAHS, 35 an apparent explanation for the observed decrease of AHI 6 months later is that 12 of 16 current smokers in our study stopped smoking, with most of them included in the group of the 22 with decreased AHI 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia is closely related to an increase in central sympathetic activity. 2,15 Sympathetic afferents residing in the myocardial wall are triggered by a number of substances released during ischemia. 3 -5 When afferent stimulation is sufficient, a reflex mechanism ensues, increasing central sympathetic outflow, with the degree of ischemia being correlated with the degree of central sympathoexcitation.…”
Section: Discussionmentioning
confidence: 99%
“…3 -5 When afferent stimulation is sufficient, a reflex mechanism ensues, increasing central sympathetic outflow, with the degree of ischemia being correlated with the degree of central sympathoexcitation. 2 This state of increased sympathetic tone seems to persist beyond the ischemic event. 1 To our knowledge, there are no studies that have shown that reversal of ischemia by PCI reduces central sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations